Integrated analysis of methylome, transcriptome and miRNAome of three pig breeds. (25th April 2018) - Fu, Yuhua; Li, Jingxuan; Tang, Qianzi; Zou, Cheng; Shen, Linyuan; Jin, Long; Li, Cencen; Fang, Chengchi; Liu, Rui; Li, Mingzhou; Zhao, Shuhong; Li, Changchun
Aim: Integrated analysis of methylome and transcriptome may help understand the molecular basis of the different breeds with different traits of commercial interest.Materials & methods: We obtained the first genome-wide methylome with single-base resolution, miRNAome and transcriptome from three swine breeds.Results: We displayed the landscape of the three omics in the whole-genome level. Integrated outcomes of methylome with genetic selection, miRNAome and transcriptome are also provided. Finally, we identified 11 candidate differentially methylated genes associated with phenotype variance in pigs.Conclusion: DNA methylation not only suppresses transcriptome but also miRNAome. The different -omics data have complicated interaction in directly or indirectly and exhibited close relations with the distinct phenotypic traits of growth, disease resistance and energy metabolism.